Volcanoes [electronic resource] : eruptions and other volcanic hazards - Kusky, Timothy M. (Hazardous earth, 2008)
A comprehensive study of volcanoes that discusses historical disasters, how the threat of volcanic hazards is reduced, plate tectonics, types of magma, eruptions and landforms, classification of igneous rocks, and prediction efforts